Peran Kepemimpinan Kepala Sekolah Terhadap Mutu Pendidikan - Fetia Nurul Hidayat; Rugaiyah (Cetta: Jurnal Ilmu Pendidikan, 2023)
Improving the quality of education must begin at the lowest level of the education unit. Effective, efficient and collaborative principal leadership is needed in schools so that the quality of Education is maintained and also improved. In the issue of independence and creativity in school education management is very dependent on the reliability of a principal, where the principal has greater authority to make decisions related to school management policies compared to the education management system managed by the central government. Meanwhile, in terms of openness, accountability of school management, the principal as a manager in managing and managing the school should pay attention to school management inputs. The purpose of this study is to see the impact of school principal leadership on the quality of Education. This research is a type of literature study with descriptive method. The results of Synergy Research and collaboration between the leadership of the principal with all school residents absolutely must be done. Because the results of synergy and collaboration have a great influence on the process of improving the quality of education within the educational unit. Things like this need to be committed together. So that the impact of these results can be felt throughout the school community, especially the quality of schools in various aspects.